ADHERENCE TO THE WHO CRITERIA ON DRUG PROMOTION LITERATURE: AN EVALUATION OF PHARMACEUTICAL ADVERTISING AT A TERTIARY HEALTHCARE FACILITY IN NORTH INDIA - DIXIT, MADHUMITA; SHARMA, KARTIKEY; CHAURASIA, RAKESH CHANDRA; NIM, DWIVIDENDRA KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This research seeks to evaluate how closely drug promotional materials at a tertiary care center in North India follow the WHO’s ethical standards. Methods: A cross-sectional analysis was carried out, involving the organized gathering of drug promotion literatures (DPLs) from the healthcare institution over a specific timeframe. A checklist, derived directly from the WHO’s guidelines for ethical drug promotion, was used to evaluate the DPLs’ content. The data were thoroughly examined to determine the degree of adherence to the WHO standards. Results: In an analysis of 149 DPLs, all included both generic and brand names. Information on the amount of active ingredient and therapeutic applications was present in 91% and 86% of the DPLs, respectively, and dosage forms appeared in 91%, with the remainder depicted pictorially. Only 32% of DPLs described the pharmacological mechanism. Details about side effects and significant adverse drug reactions, as well as precautions and warnings, contraindications, and major drug interactions, were included in 19%, 16%, 18%, and 11% of DPLs, respectively. The manufacturer’s name was mentioned in 72% of the documents, while the manufacturer’s address appeared in 26%. References to scientific literature were included in just 29% of the DPLs. Conclusion: This research highlights the need for improved oversight and regulation of drug promotion activities within the healthcare facility. Less than 20% of DPLs provide information on drug safety. Compliance with the WHO standards is crucial for ethical drug promotion, protecting patient care, and maintaining the integrity of healthcare services. Cooperative initiatives among healthcare facilities, pharmaceutical firms, and regulatory agencies are urgently required.